ABS flame retardant toughening agent and preparation method and application thereof
By using modified nano-aluminum hydroxide particles in ABS plastics to react with other chemical substances, ABS flame retardant toughening agent was prepared, which solved the problem that ABS plastics are difficult to achieve high flame retardant effects in halogen-free flame retardant, and achieved high flame retardancy and toughening of the material.
Patent Information
- Application Number
- CN202411106138.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-08-13
AI Technical Summary
When using halogen-free flame retardant, it is difficult to achieve the V-0 flame retardant effect, and it also has a great pollution to the environment. In addition, the existing phosphorus-based and inorganic flame retardant affect the impact and heat resistance of the material when improving flame retardancy.
ABS flame retardant toughener was prepared by modifying silane coupling agent on the surface of nano-aluminum hydroxide particles and reacting with benzaldehyde and 9,10-dihydro-9-oxa-10-phosphophenophen-10-oxide, combining polydopamine and long-chain silane.
It significantly improves the flame retardant effect of ABS plastics, and plays a linking buffer between the molecular chains, reduces cracks, improves the toughness and heat resistance of the material, and is suitable for the wide application of ABS plastics.
Smart Images

Figure BDA0004990860840000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastics, and in particular to an ABS flame retardant toughening agent and a preparation method and application thereof. Background Art
[0002] Acrylonitrile-butadiene-styrene plastic (ABS) plastic has good heat resistance, high impact resistance and excellent processability, and is widely used in automotive parts, home appliances and electronic components. Materials used for housings of home appliances and office automation equipment have flame retardant requirements, and halogen compounds are usually added to provide flame retardancy. Halogen flame retardants have a good balance of cost and performance, a wide range of applications, and are moderately priced, but may be harmful to the environment.
[0003] Due to the lack of aromatic groups on the main chain of ABS molecules, it is difficult to achieve V-0 level with halogen-free flame retardants, and it seriously pollutes the environment. The international research on halogen-free ABS has been carried out for many years, mainly using phosphorus-based flame retardants or inorganic flame retardants. Phosphorus-based flame retardants are highly efficient and require a small amount of addition, but the addition of organic phosphorus plasticizes the material, seriously deteriorating the impact and heat resistance of the material; inorganic flame retardants have low flame retardant efficiency and require a large amount of addition. Although they have little effect on heat resistance, they seriously affect impact. Summary of the invention
[0004] The purpose of the present invention is to provide an ABS flame retardant and toughening agent and a preparation method and application thereof. The composite flame retardant is made of an organic flame retardant and an inorganic flame retardant, which can significantly improve the flame retardant effect of ABS plastics, and can also play a connecting and buffering role between molecular chains, reduce cracks, have a good toughening effect, and can be widely used in ABS plastics.
[0005] The technical solution of the present invention is achieved in this way:
[0006] The invention provides a method for preparing an ABS flame retardant and toughening agent. The surface of nano aluminum hydroxide particles doped with Ti element is modified with a silane coupling agent, reacted with benzaldehyde and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and then reacted with long-chain silane after surface polydopamine modification to prepare the ABS flame retardant and toughening agent.
[0007] As a further improvement of the present invention, the following steps are included:
[0008] S1. Aluminum chloride solution was added dropwise to the alkali solution, heated and stirred to react, at which time the solution pH was 6.2-6.5, tetrabutyl titanate ethanol solution was added dropwise, stirred to react, centrifuged, washed, and dried to obtain nanoparticles;
[0009] S2. adding the composite silane coupling agent to ethanol, adding the nanoparticles, heating and stirring the reaction, centrifuging, washing, and drying to obtain modified nanoparticles;
[0010] S3. The modified nanoparticles were heated and stirred to react with benzaldehyde, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added, and the reaction was stirred to obtain organophosphine-modified nanoparticles;
[0011] S4. The organophosphine-modified nanoparticles are added to water, dopamine hydrochloride and a catalyst are added, and the reaction is heated and stirred to obtain polydopamine-coated modified particles;
[0012] S5. Add the polydopamine-coated modified particles into ethanol, add long-chain silane, heat and stir to react, and obtain an ABS flame retardant toughening agent.
[0013] As a further improvement of the present invention, the alkali solution in step S1 is a 1-2 mol / L NaOH or KOH solution, the mass ratio of the alkali solution, aluminum chloride, and tetrabutyl titanate is 100:4-7:1-2, the temperature of the heating and stirring reaction is 70-80°C, the time is 0.5-1h, and the stirring reaction time is 1-2h.
[0014] As a further improvement of the present invention, the mass ratio of the composite silane coupling agent and the nanoparticles in step S2 is 2-3:10, the temperature of the heating and stirring reaction is 40-50°C, the time is 1-3h, and the composite silane coupling agent is a mixture of KH560 and KH550, and the mass ratio is 10-12:7-9.
[0015] As a further improvement of the present invention, the mass ratio of the modified nanoparticles, benzaldehyde and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in step S3 is 10:1.5-3.2:4-5, the temperature of the heating and stirring reaction is 75-85°C, the time is 3-5h, and the stirring reaction time is 10-12h.
[0016] As a further improvement of the present invention,.
[0017] As a further improvement of the present invention, the mass ratio of the organic phosphine modified nanoparticles, dopamine hydrochloride and catalyst in step S4 is 10:1-2:0.1-0.2, the catalyst is a Tris-HCl solution with a pH of 7.5-8.5, the temperature of the heating and stirring reaction is 40-50°C, and the time is 3-5h.
[0018] As a further improvement of the present invention, the mass ratio of the polydopamine-coated modified particles and the long-chain silane in step S5 is 12-15:2-3, and the long-chain silane is at least one of dodecyl (methyl) dimethoxy silane, dodecyl trimethoxy silane, dodecyl triethoxy silane, tetradecyl trimethoxy silane, tetradecyl triethoxy silane, hexadecyl trimethoxy silane and hexadecyl triethoxy silane; the temperature of the heating and stirring reaction is 35-45°C, and the time is 2-4h.
[0019] As a further improvement of the present invention, the present invention specifically comprises the following steps:
[0020] S1. Add 20 parts by weight of a solution containing 4-7 parts by weight of aluminum chloride to 100 parts by weight of a 1-2 mol / L NaOH or KOH solution, heat to 70-80°C, stir and react for 0.5-1h, at which time the pH value of the solution is 6.2-6.5, add 20 parts by weight of an ethanol solution containing 1-2 parts by weight of tetrabutyl titanate, stir and react for 1-2h, centrifuge, wash, and dry to obtain nanoparticles;
[0021] S2. Add 2-3 parts by weight of a composite silane coupling agent to ethanol, add 10 parts by weight of nanoparticles, heat to 40-50 ° C, stir the reaction for 1-3h, centrifuge, wash, and dry to obtain modified nanoparticles;
[0022] The composite silane coupling agent is a mixture of KH560 and KH550, with a mass ratio of 10-12:7-9;
[0023] S3. 10 parts by weight of modified nanoparticles and 1.5-3.2 parts by weight of benzaldehyde are added to toluene, heated to 75-85 ° C, stirred for 3-5 hours, 4-5 parts by weight of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are added, stirred for 10-12 hours to obtain organophosphine-modified nanoparticles;
[0024] S4. 10 parts by weight of the organic phosphine-modified nanoparticles are added to water, 1-2 parts by weight of dopamine hydrochloride and 0.1-0.2 parts by weight of a catalyst are added, heated to 40-50 ° C, stirred for 3-5h, to obtain polydopamine-coated modified particles;
[0025] The catalyst is a Tris-HCl solution with a pH of 7.5-8.5;
[0026] S5. Add 12-15 parts by weight of the polydopamine-coated modified particles to ethanol, add 2-3 parts by weight of long-chain silane, heat to 35-45° C., stir and react for 2-4 hours to obtain an ABS flame retardant toughening agent.
[0027] The present invention further protects an ABS flame retardant toughening agent prepared by the above preparation method.
[0028] The present invention further protects the use of the above-mentioned ABS flame retardant and toughening agent in improving the flame retardancy and toughness of ABS composite materials.
[0029] The present invention has the following beneficial effects:
[0030] The nano aluminum hydroxide prepared by the invention is a good inorganic flame retardant. After adding tetrabutyl titanate to react, the prepared nano particles can be doped with titanium element. When added to ABS plastic, the antibacterial, anti-aging and anti-ultraviolet properties of the material can be significantly improved, while the flame retardancy can also be improved, and the flame retardancy has a synergistic flame retardant effect.
[0031] The surface of the prepared nanoparticles is modified by composite silane coupling agents KH560 and KH550, and the surface has epoxy groups and amino groups. The amino groups can react with benzaldehyde to form N=C bonds in step S3, and then the epoxy groups and N=C bonds can react with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) to connect 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to the surface of the nanoparticles, thereby preparing nanoparticles containing organic phosphine.
[0032] The surface is further modified by polydopamine, which greatly increases the N content in the flame retardant. While improving the flame retardant effect, it also significantly improves the compatibility of the ABS flame retardant toughening agent in ABS plastic. At the same time, it has the function of capturing free radicals, which enhances the material's heat resistance, UV resistance, and aging resistance. Due to its good adhesion, it can reduce the formation of cracks due to stress and improve the toughness of ABS plastic. The surface is further modified by long-chain silane. The long chain can not only further improve the compatibility, but also play a connecting and buffering role between molecular chains, reducing the development of silver streaks into cracks due to stress, and playing a toughening effect.
[0033] The ABS flame retardant toughening agent prepared by the invention is a composite flame retardant prepared by an organic flame retardant and an inorganic flame retardant, which can significantly improve the flame retardant effect of ABS plastics, and can also play a connecting and buffering role between molecular chains, reduce cracks, have a good toughening effect, and can be widely used in ABS plastics. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] This embodiment provides a method for preparing an ABS flame retardant toughening agent, which specifically comprises the following steps:
[0037] S1. Add 20 g of a solution containing 4 g of aluminum chloride to 100 g of a 1 mol / L NaOH solution, heat to 70 ° C, and stir for 0.5 h. At this time, the pH value of the solution is 6.5. Add 20 g of an ethanol solution containing 1 g of tetrabutyl titanate, stir for 1 h, centrifuge, wash, and dry to obtain nanoparticles.
[0038] S2. Add 2 g of the composite silane coupling agent to 150 mL of ethanol, add 10 g of nanoparticles, heat to 40 ° C, stir and react for 1 h, centrifuge, wash, and dry to obtain modified nanoparticles;
[0039] The composite silane coupling agent is a mixture of KH560 and KH550, with a mass ratio of 10:7;
[0040] S3. 10 g of modified nanoparticles and 1.5 g of benzaldehyde were added to 200 mL of toluene, heated to 75 ° C, stirred for 3 h, 4 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added, stirred for 10 h, centrifuged, washed, and dried to obtain organophosphine-modified nanoparticles;
[0041] S4. 10 g of the organophosphine-modified nanoparticles were added to 200 mL of water, 1 g of dopamine hydrochloride and 0.1 g of the catalyst were added, heated to 40 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain polydopamine-coated modified particles;
[0042] The catalyst is a Tris-HCl solution with a pH of 7.5;
[0043] S5. Add 12 g of polydopamine-coated modified particles into 200 mL of ethanol, add 2 g of dodecyltriethoxysilane, heat to 35° C., stir to react for 2 h, centrifuge, wash, and dry to obtain an ABS flame retardant toughening agent.
[0044] Example 2
[0045] This embodiment provides a method for preparing an ABS flame retardant toughening agent, which specifically comprises the following steps:
[0046] S1. Add 20 g of a solution containing 7 g of aluminum chloride to 100 g of a 2 mol / L KOH solution, heat to 80 ° C, and stir for 1 h. At this time, the pH value of the solution is 6.2. Add 20 g of an ethanol solution containing 2 g of tetrabutyl titanate, stir for 2 h, centrifuge, wash, and dry to obtain nanoparticles.
[0047] S2. Add 3 g of the composite silane coupling agent to 150 mL of ethanol, add 10 g of nanoparticles, heat to 50 ° C, stir and react for 3 h, centrifuge, wash, and dry to obtain modified nanoparticles;
[0048] The composite silane coupling agent is a mixture of KH560 and KH550, with a mass ratio of 12:9;
[0049] S3. 10 g of modified nanoparticles and 3.2 g of benzaldehyde were added to 200 mL of toluene, heated to 85 ° C, stirred for 5 h, 5 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added, stirred for 12 h, centrifuged, washed, and dried to obtain organophosphine-modified nanoparticles;
[0050] S4. 10 g of the organophosphine-modified nanoparticles were added to 200 mL of water, 2 g of dopamine hydrochloride and 0.2 g of the catalyst were added, heated to 50 ° C, stirred for 5 h, centrifuged, washed, and dried to obtain polydopamine-coated modified particles;
[0051] The catalyst is a Tris-HCl solution with a pH of 8.5;
[0052] S5. Add 15 g of polydopamine-coated modified particles into 200 mL of ethanol, add 3 g of dodecyltrimethoxysilane, heat to 45° C., stir to react for 4 h, centrifuge, wash, and dry to obtain an ABS flame retardant toughening agent.
[0053] Example 3
[0054] This embodiment provides a method for preparing an ABS flame retardant toughening agent, which specifically comprises the following steps:
[0055] S1. 20 g of 5.5 g of aluminum chloride solution was added dropwise to 100 g of 1.5 mol / L NaOH solution, heated to 75 ° C, stirred for 1 h, at which time the pH value of the solution was 6.3, 20 g of 1.5 g of tetrabutyl titanate ethanol solution was added dropwise, stirred for 1.5 h, centrifuged, washed, and dried to obtain nanoparticles;
[0056] S2. Add 2.5 g of the composite silane coupling agent to 150 mL of ethanol, add 10 g of nanoparticles, heat to 45 ° C, stir and react for 2 h, centrifuge, wash, and dry to obtain modified nanoparticles;
[0057] The composite silane coupling agent is a mixture of KH560 and KH550, with a mass ratio of 11:8;
[0058] S3. 10 g of modified nanoparticles and 2.5 g of benzaldehyde were added to 200 mL of toluene, heated to 80 ° C, stirred for 4 h, 4.5 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added, stirred for 11 h, centrifuged, washed, and dried to obtain organophosphine-modified nanoparticles;
[0059] S4. 10 g of the organophosphine-modified nanoparticles were added to 200 mL of water, 1.5 g of dopamine hydrochloride and 0.15 g of the catalyst were added, heated to 45 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain polydopamine-coated modified particles;
[0060] The catalyst is a Tris-HCl solution with a pH of 8;
[0061] S5. Add 13 g of polydopamine-coated modified particles into 200 mL of ethanol, add 2.5 g of dodecyl(methyl)dimethoxysilane, heat to 40° C., stir to react for 3 h, centrifuge, wash, and dry to obtain an ABS flame retardant toughening agent.
[0062] Example 4
[0063] Compared with Example 3, the difference is that the composite silane coupling agent is replaced by a single KH560.
[0064] Example 5
[0065] Compared with Example 3, the difference is that the composite silane coupling agent is replaced by a single KH550.
[0066] Comparative Example 1
[0067] Compared with Example 3, the difference is that tetrabutyl titanate is not added in step S1.
[0068] The details are as follows:
[0069] S1. Add 20 g of 5.5 g aluminum chloride solution to 100 g of 1.5 mol / L NaOH solution, heat to 75 ° C, stir and react for 1 h, at which time the pH value of the solution is 6.3, centrifuge, wash, and dry to obtain nanoparticles;
[0070] S2. Add 2.5 g of the composite silane coupling agent to 150 mL of ethanol, add 10 g of nanoparticles, heat to 45 ° C, stir and react for 2 h, centrifuge, wash, and dry to obtain modified nanoparticles;
[0071] The composite silane coupling agent is a mixture of KH560 and KH550, with a mass ratio of 11:8;
[0072] S3. 10 g of modified nanoparticles and 2.5 g of benzaldehyde were added to 200 mL of toluene, heated to 80 ° C, stirred for 4 h, 4.5 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added, stirred for 11 h, centrifuged, washed, and dried to obtain organophosphine-modified nanoparticles;
[0073] S4. 10 g of the organophosphine-modified nanoparticles were added to 200 mL of water, 1.5 g of dopamine hydrochloride and 0.15 g of the catalyst were added, heated to 45 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain polydopamine-coated modified particles;
[0074] The catalyst is a Tris-HCl solution with a pH of 8;
[0075] S5. Add 13 g of polydopamine-coated modified particles into 200 mL of ethanol, add 2.5 g of dodecyl(methyl)dimethoxysilane, heat to 40° C., stir to react for 3 h, centrifuge, wash, and dry to obtain an ABS flame retardant toughening agent.
[0076] Comparative Example 2
[0077] Compared with Example 3, the difference is that steps S2 and S3 are not performed.
[0078] The details are as follows:
[0079] S1. 20 g of 5.5 g of aluminum chloride solution was added dropwise to 100 g of 1.5 mol / L NaOH solution, heated to 75 ° C, stirred for 1 h, at which time the pH value of the solution was 6.3, 20 g of 1.5 g of tetrabutyl titanate ethanol solution was added dropwise, stirred for 1.5 h, centrifuged, washed, and dried to obtain nanoparticles;
[0080] S2. 10 g of nanoparticles were added to 200 mL of water, 1.5 g of dopamine hydrochloride and 0.15 g of catalyst, heated to 45 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain polydopamine-coated particles;
[0081] The catalyst is a Tris-HCl solution with a pH of 8;
[0082] S3. Add 13 g of polydopamine-coated particles into 200 mL of ethanol, add 2.5 g of dodecyl(methyl)dimethoxysilane, heat to 40° C., stir to react for 3 h, centrifuge, wash, and dry to obtain an ABS flame retardant toughening agent.
[0083] Comparative Example 3
[0084] Compared with Example 3, the difference is that step S3 is not performed.
[0085] The details are as follows:
[0086] S1. 20 g of 5.5 g of aluminum chloride solution was added dropwise to 100 g of 1.5 mol / L NaOH solution, heated to 75 ° C, stirred for 1 h, at which time the pH value of the solution was 6.3, 20 g of 1.5 g of tetrabutyl titanate ethanol solution was added dropwise, stirred for 1.5 h, centrifuged, washed, and dried to obtain nanoparticles;
[0087] S2. Add 2.5 g of the composite silane coupling agent to 150 mL of ethanol, add 10 g of nanoparticles, heat to 45 ° C, stir and react for 2 h, centrifuge, wash, and dry to obtain modified nanoparticles;
[0088] The composite silane coupling agent is a mixture of KH560 and KH550, with a mass ratio of 11:8;
[0089] S3. 10 g of modified nanoparticles were added to 200 mL of water, 1.5 g of dopamine hydrochloride and 0.15 g of catalyst were added, heated to 45 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain polydopamine-coated modified particles;
[0090] The catalyst is a Tris-HCl solution with a pH of 8;
[0091] S4. Add 13 g of polydopamine-coated modified particles into 200 mL of ethanol, add 2.5 g of dodecyl(methyl)dimethoxysilane, heat to 40° C., stir to react for 3 h, centrifuge, wash, and dry to obtain an ABS flame retardant toughening agent.
[0092] Comparative Example 4
[0093] Compared with Example 3, the difference is that step S4 is not performed.
[0094] The details are as follows:
[0095] S1. 20 g of 5.5 g of aluminum chloride solution was added dropwise to 100 g of 1.5 mol / L NaOH solution, heated to 75 ° C, stirred for 1 h, at which time the pH value of the solution was 6.3, 20 g of 1.5 g of tetrabutyl titanate ethanol solution was added dropwise, stirred for 1.5 h, centrifuged, washed, and dried to obtain nanoparticles;
[0096] S2. Add 2.5 g of the composite silane coupling agent to 150 mL of ethanol, add 10 g of nanoparticles, heat to 45 ° C, stir and react for 2 h, centrifuge, wash, and dry to obtain modified nanoparticles;
[0097] The composite silane coupling agent is a mixture of KH560 and KH550, with a mass ratio of 11:8;
[0098] S3. 10 g of modified nanoparticles and 2.5 g of benzaldehyde were added to 200 mL of toluene, heated to 80 ° C, stirred for 4 h, 4.5 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added, stirred for 11 h, centrifuged, washed, and dried to obtain organophosphine-modified nanoparticles;
[0099] S4. Add 13 g of the organophosphine-modified particles to 200 mL of ethanol, add 2.5 g of dodecyl(methyl)dimethoxysilane, heat to 40° C., stir to react for 3 h, centrifuge, wash, and dry to obtain an ABS flame retardant toughening agent.
[0100] Comparative Example 5
[0101] Compared with Embodiment 3, the difference is that step S5 is not performed.
[0102] The details are as follows:
[0103] S1. 20 g of 5.5 g of aluminum chloride solution was added dropwise to 100 g of 1.5 mol / L NaOH solution, heated to 75 ° C, stirred for 1 h, at which time the pH value of the solution was 6.3, 20 g of 1.5 g of tetrabutyl titanate ethanol solution was added dropwise, stirred for 1.5 h, centrifuged, washed, and dried to obtain nanoparticles;
[0104] S2. Add 2.5 g of the composite silane coupling agent to 150 mL of ethanol, add 10 g of nanoparticles, heat to 45 ° C, stir and react for 2 h, centrifuge, wash, and dry to obtain modified nanoparticles;
[0105] The composite silane coupling agent is a mixture of KH560 and KH550, with a mass ratio of 11:8;
[0106] S3. 10 g of modified nanoparticles and 2.5 g of benzaldehyde were added to 200 mL of toluene, heated to 80 ° C, stirred for 4 h, 4.5 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added, stirred for 11 h, centrifuged, washed, and dried to obtain organophosphine-modified nanoparticles;
[0107] S4. Add 10 g of organic phosphine-modified nanoparticles to 200 mL of water, add 1.5 g of dopamine hydrochloride and 0.15 g of catalyst, heat to 45 ° C, stir and react for 4 h, centrifuge, wash, and dry to obtain polydopamine-coated modified particles, which are ABS flame retardant toughening agents;
[0108] The catalyst is a Tris-HCl solution with a pH of 8.
[0109] Test Example 1
[0110] The ABS flame retardant toughening agent prepared in Examples 1-5 and Comparative Examples 1-5 was added to acrylonitrile-styrene-butadiene copolymer resin (ABS resin, Chimei PA-757F, Dongguan Guanxin Plastic Co., Ltd.) at a content of 2wt%, mixed at 85°C for 10min by a high-speed mixer, placed in a HAKKE torque rheometer for mixing for 10min, and the processing temperature was set to 200°C. After mixing, the sample was cooled to room temperature, crushed, and the crushed sample was pressed into samples of various thicknesses, and cut into specimens of various specifications required for various tests.
[0111] Vertical burning (UL94) test: tested in accordance with GB / T2408-2021, the specimen size is 125mm×13mm×3.2mm;
[0112] The Izod notched impact strength is tested according to ISO 180-2000, using A-type notch, 8mm notch retention width, and pendulum energy of 2.75J;
[0113] The tensile properties were tested according to GB / T1040-2006, with a tensile speed of 50 mm / min, a specimen thickness of 2 mm, a narrow portion width of 4 mm, and each group was tested 3 times, and the average value of the results was taken.
[0114] The results are shown in Table 1.
[0115] Table 1
[0116]
[0117] It can be seen from the above table that the ABS flame retardant toughening agent prepared in Examples 1-3 of the present invention can significantly improve the flame retardancy and mechanical properties of ABS resin.
[0118] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an ABS flame retardant toughening agent, characterized in that: The surface of Ti-doped nano-aluminum hydroxide particles was modified with a silane coupling agent, reacted with benzaldehyde and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and then reacted with long-chain silane after being modified with polydopamine to prepare an ABS flame retardant toughening agent. The following steps are involved: S1. Aluminum chloride solution was added dropwise to the alkali solution, heated and stirred to react, at which time the solution pH was 6.2-6.5, tetrabutyl titanate ethanol solution was added dropwise, stirred to react, centrifuged, washed, and dried to obtain nanoparticles; S2. The composite silane coupling agent is added to ethanol, the nanoparticles are added, the reaction is heated and stirred, centrifuged, washed, and dried to obtain modified nanoparticles; the mass ratio of the composite silane coupling agent to the nanoparticles is 2-3:10, and the composite silane coupling agent is a mixture of KH560 and KH550, and the mass ratio is 10-12:7-9; S3. The modified nanoparticles were heated and stirred to react with benzaldehyde, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added, and the reaction was stirred to obtain organophosphine-modified nanoparticles; S4. The organophosphine-modified nanoparticles are added to water, dopamine hydrochloride and a catalyst are added, and the reaction is heated and stirred to obtain polydopamine-coated modified particles; S5. Add polydopamine coated modified particles to ethanol, add long-chain silane, heat and stir to react, and obtain ABS flame retardant toughening agent; the mass ratio of the polydopamine coated modified particles and the long-chain silane is 12-15:2-3, and the long-chain silane is at least one of dodecyl (methyl) dimethoxy silane, dodecyl trimethoxy silane, dodecyl triethoxy silane, tetradecyl trimethoxy silane, tetradecyl triethoxy silane, hexadecyl trimethoxy silane and hexadecyl triethoxy silane.
2. The preparation method according to claim 1, characterized in that: The alkali solution in step S1 is 1-2 mol / L NaOH or KOH solution, the mass ratio of the alkali solution, aluminum chloride and tetrabutyl titanate is 100:4-7:1-2, the temperature of the heating and stirring reaction is 70-80°C, the time is 0.5-1h, and the stirring reaction time is 1-2h.
3. The preparation method according to claim 1, characterized in that: The temperature of the heating and stirring reaction in step S2 is 40-50° C. and the time is 1-3 h.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the modified nanoparticles, benzaldehyde and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in step S3 is 10:1.5-3.2:4-5, the temperature of the heating and stirring reaction is 75-85°C, the time is 3-5h, and the stirring reaction time is 10-12h.
5. The preparation method according to claim 1, characterized in that: In step S4, the mass ratio of the organic phosphine modified nanoparticles, dopamine hydrochloride and catalyst is 10:1-2:0.1-0.2, the catalyst is a Tris-HCl solution with a pH of 7.5-8.5, the temperature of the heating and stirring reaction is 40-50°C, and the time is 3-5h.
6. The preparation method according to claim 1, characterized in that: The temperature of the heating and stirring reaction in step S5 is 35-45° C. and the time is 2-4 hours.
7. The preparation method according to claim 1, characterized in that: The specific steps include: S1. Add 20 parts by weight of a solution containing 4-7 parts by weight of aluminum chloride to 100 parts by weight of a 1-2 mol / L NaOH or KOH solution, heat to 70-80°C, stir and react for 0.5-1h, at which time the pH value of the solution is 6.2-6.5, add 20 parts by weight of an ethanol solution containing 1-2 parts by weight of tetrabutyl titanate, stir and react for 1-2h, centrifuge, wash, and dry to obtain nanoparticles; S2. Add 2-3 parts by weight of a composite silane coupling agent to ethanol, add 10 parts by weight of nanoparticles, heat to 40-50 ° C, stir the reaction for 1-3h, centrifuge, wash, and dry to obtain modified nanoparticles; The composite silane coupling agent is a mixture of KH560 and KH550, with a mass ratio of 10-12:7-9; S3. 10 parts by weight of modified nanoparticles and 1.5-3.2 parts by weight of benzaldehyde are added to toluene, heated to 75-85 ° C, stirred for 3-5 hours, 4-5 parts by weight of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide are added, stirred for 10-12 hours to obtain organophosphine-modified nanoparticles; S4. 10 parts by weight of the organic phosphine-modified nanoparticles are added to water, 1-2 parts by weight of dopamine hydrochloride and 0.1-0.2 parts by weight of a catalyst are added, heated to 40-50 ° C, stirred for 3-5h, to obtain polydopamine-coated modified particles; The catalyst is a Tris-HCl solution with a pH of 7.5-8.5; S5. Add 12-15 parts by weight of the polydopamine-coated modified particles to ethanol, add 2-3 parts by weight of long-chain silane, heat to 35-45° C., stir and react for 2-4 hours to obtain an ABS flame retardant toughening agent.
8. An ABS flame retardant toughening agent prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the ABS flame retardant and toughening agent as claimed in claim 8 in improving the flame retardancy and toughness of ABS composite materials.
Citation Information
Patent Citations
Modified inorganic flame retardant, preparation method and application of modified inorganic flame retardant in plastic products
CN105837860A
Antibacterial flame-retardant plastic, preparation method thereof and food bottle prepared from antibacterial flame-retardant plastic
CN117362834A